2020
DOI: 10.4274/tjo.galenos.2019.95871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Upper Eyelid Blepharoplasty on Contrast Sensitivity in Dermatochalasis Patients

Abstract: Objectives: To evaluate the impact of upper eyelid blepharoplasty on contrast sensitivity in dermatochalasis patients. Materials and Methods: Best corrected visual acuity, ophthalmologic examination, eyelid examination, lash ptosis, contrast sensitivity using sine-wave contrast sensitivity chart, keratometric parameters, and corneal aberrations of 34 eyes of 34 patients who underwent upper eyelid blepharoplasty due to dermatochalasis in our clinic between the years 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…As observed by Dogan et al 10 in patients undergoing upper eyelid blepharoplasty, the only significant difference in corneal topography was a change of 0.3 D in K2 values at postoperative 1 month in the group undergoing levator surgery, but this change did not persist at postoperative 3 and 6 months. Similar to the studies by Dogan et al 10 and Nalcı et al 11 , we detected no other significant postoperative changes in other keratometric values.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As observed by Dogan et al 10 in patients undergoing upper eyelid blepharoplasty, the only significant difference in corneal topography was a change of 0.3 D in K2 values at postoperative 1 month in the group undergoing levator surgery, but this change did not persist at postoperative 3 and 6 months. Similar to the studies by Dogan et al 10 and Nalcı et al 11 , we detected no other significant postoperative changes in other keratometric values.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have also evaluated the effects of upper eyelid surgery on corneal topography. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 27 In a study by Zinkernager et al 5 , patients undergoing surgery for dermatochalasis or ptosis were divided into three groups according to the surgery performed: ptosis repair by levator surgery, blepharoplasty performed with skin-only removal, and blepharoplasty with skin and fat pad removal. At postoperative 3 months, they detected astigmatic changes of 0.19 D in the blepharoplasty with fat pad reduction group and 0.25 D in the ptosis repair by levator surgery group, while no statistically significant change was detected in the astigmatic axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in their study, as in the present study, Nalci et al [22] found no significant changes in K1 and K2 values in the third postoperative-month of patients who had blepharoplasty surgery relative to the pre-operative period. It is remarkable that a similar mean age was detected in the patients of both our study and the study by Nalci et al Similar to our study, the fact that the results of the blephroplasty surgery did not cause a significant change on the keratometric values can be explained by the fact that the ages of the patients who underwent surgery in our study and Nalci et al's study were similar.…”
Section: Discussionsupporting
confidence: 85%
“…In a recently published study similar to ours, no significant difference was observed between pre-and post-operative keratometric values and astigmatism grades. 16 There are a few publications on the effect of upper eyelid diseases on corneal HOAs. A study examining the effects of chalazion excision on corneal aberrations showed a decrease in RMS total values, vertical-horizontal trefoil, and horizontal coma postoperatively.…”
Section: Discussionmentioning
confidence: 99%